Polymicrobial Interactions Induce Multidrug Tolerance in Staphylococcus aureus Through Energy Depletion - Nabb, Dan L.; Song, Seoyoung; Kluthe, Kennedy E.; Daubert, Trevor A.; Luedtke, Brandon E.; Nuxoll, Austin S. (Frontiers in Microbiology, 2019)
Staphylococcus aureus is responsible for a high number of relapsing infections, which are often mediated by the protective nature of biofilms. Polymicrobial biofilms appear to be more tolerant to antibiotic treatment, however, the underlying mechanisms for this remain unclear. Polymicrobial biofilm and planktonic cultures formed by S. aureus and Candida albicans are 10- to 100-fold more tolerant to oxacillin, vancomycin, ciprofloxacin, delafloxacin, and rifampicin compared to monocultures of S. aureus. The possibility of C. albicans matrix components physically blocking antibiotic molecules from reaching S. aureus was ruled out as oxacillin, ciprofloxacin, delafloxacin, and rifampicin were able to diffuse through polymicrobial biofilms. Based on previous findings that S. aureus forms drug tolerant persister cells through ATP depletion, we examined nutrient deprivation by determining glucose availability, which indirectly correlates to ATP production via the tricarboxylic acid (TCA) cycle. Using an extracellular glucose assay, we confirmed that S. aureus and C. albicans polymicrobial cultures depleted available glucose faster than the respective monocultures. Supporting this finding, S. aureus exhibited decreased TCA cycle activity, specifically fumarase expression, when grown in the presence of C. albicans. In addition, S. aureus grown in polymicrobial cultures displayed 2.2 fold more cells with low membrane potential and a 13% reduction in intracellular ATP concentrations than in monocultures. Collectively, these data demonstrate that decreased metabolic activity through nutrient deprivation is a mechanism for increased antibiotic tolerance within polymicrobial cultures.